Exercise in patients admitted for decompensated heart failure - cardiac rehabilitation - Delgado, Bruno (2018)
Heart failure (HF) is characterized by dyspnea, fatigue and edema that leads to decreased exercise tolerance, functional dependence and impairment of performance in activities of daily living (ADL). Exercise is a well stablish intervention, for patients with stable cronic HF, which leads to improvement of symptoms, promotes functional capacity and decrease exercise intolerance. Exercise its not yet tested for patients during the phase of stabilization. Purpose: To evaluate the safety and feasibility of an aerobic exercise training program for patients admitted due to decompensated HF: the ERIC program. Methods: Patients are randomized in training group (TG) or control (CG). Data includes cardiovascular history, HF history and two functional tools: London Chest of Daily Living Activities (LCADL) and Barthel Index (BI). TG patients perform the ERIC program twice a day, 6 days a week. ERIC program is a supervised aerobic exercise program, with increasing levels of intensity, divided into 5 stages: respiratory raining, gait training and climbing stairs, for progressive duration periods. In all sessions are valuated vital signs before and after the exercise, as well as Borg Modified Perceived Exertion scale. CG patients are supervised too and perform freely physical activity. At discharge, all patients perform a 6 minute walking test (6MWT), and evaluation of LCADL scale and BI. Results: Until now, 47 patients are randomized (24 in TG - 275 sessions) with an average age of 71 (11) years old. 31 are male, 80% are in NHYA class III and 20% are class IV. At admission both groups (training vs control) of patients have the same level of functional dependence. At discharge, TG present lower LCADL and Borg score and higher BI score. Those differences are statistically significant (p=0,038 LCADL; p=0,024 Barthel). The average distance on 6MWT by TG is 72 meters higher, which is a statistically significant (p=0,031). No adverse events had occurred, like precordial pain, falls or worsening of clinical state. Conclusions: ERIC program can safely lead patients to a better functional capacity state.